The global burden of cardiovascular disease attributable to diet high in sugar-sweetened beverages among people aged 60 years and older: an analysis for the global burden of disease study 2019 - Jiajie Lv; Chenghao Yang; Xitao Yang (Frontiers Media S.A., 2024)
ObjectivesThis study aimed to quantify the global cardiovascular disease (CVD) burden attributable to diet high in sugar-sweetened beverages (SSB) among adults aged 60 years and older using data from the Global Burden of Disease (GBD) Study 2019.MethodsWe extracted data on CVD mortality, disability-adjusted life-years (DALYs), and risk-factor exposures from the GBD 2019 study for people aged 60 and older. Age-period-cohort models were used to estimate the overall annual percentage change in mortality and DALY rate (net drift, % per year), mortality and DALY rate for each age group from 1990 to 2019 (local drift, % per year), longitudinal age-specific rate corrected for period bias (age effect), and mortality and Daly rate for each age group from 1990 to 2019 (local drift, % per year). And period/cohort relative risk (period/cohort effect).ResultsBetween 1990 and 2019, global age-standardized CVD mortality (ASMR) and disability-adjusted life years (DALY) rates attributable to high SSB intake decreased, with larger reductions in high-SDI regions. ASMR declined from 19.5 to 13 per 100,000 (estimated annual percentage change (EAPC): −1.46%) and ASDR declined from 345.8 to 220.6 per 100,000 (EAPC: −1.66%). Age-period-cohort analysis showed CVD deaths and DALYs increased exponentially with age, peaking at 85-89 years. Period effects indicated declining CVD mortality and DALY rates since 1999, especially in higher-SDI regions. Cohort effects demonstrated consistent risk declines across successive generations born between 1900 and 1959. Predictions suggest continuing decreases through 2045 globally, but slower declines in lower-SDI regions.ConclusionIn conclusion, this comprehensive assessment of global CVD burden among older adults attributable to high SSB intake highlights major achievements but also persistent areas needing attention. Favorable declining mortality and DALY rate trends reflect substantial progress in CVD control amid population growth and aging.